Sustainabilitas Kebijakan Inisiasi Dividen pada Perusahaan-Perusahaan Go-Public di Indonesia - Sugeng, Bambang (Jurnal Aplikasi Manajemen, 2009)
This research aims at examining the influence of some variables i.e. current performance, after initiation performance, maturity, capital structure, and ownership structure, on sustainability of dividend initiation policy, and also the influence of sustainability of dividend initiation policy itself on its consequence variable i.e. stock performance. This research was conducted to sample firms consisting of 180 going public firms listed at Jakarta Stock Exchange and involving financial data which all belongs to kind of secondary data. Using Structural Equation Model (SEM) for data analysis and hypothesis testing, this research has found significant influence from after initiation performance, the only variable among four antecedent variables being examined, to sustainability of dividend initiation policy, and there is also found significant influence from sustainability of dividend initiation policy to its consequence variable i.e. stock performance. In a whole, findings of this research indicate that while signaling model of dividend is proven to be credible in explaining dividend initiation policy behavior among Indonesian going-public firms, agency cost model is not, particularly pertaining to monitoring rationale proposition (Easterbrook, 1984) and maturity proposition (Grullon, 2001). Finally, the existence of difference between finding of this research and those of ones conducted in advanced market context, basically provides supporting evidence on Frankfutter & Wood's argument stating that dividend policy is contextual in nature.